2021
DOI: 10.3389/fonc.2021.625872
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Immune Checkpoint Inhibitors in Patients With Cancer and Preexisting Autoimmune Disease

Abstract: Immune checkpoint inhibitor (ICI) is a revolutionary breakthrough in the field of cancer treatment. Because of dysregulated activation of the immune system, patients with autoimmune disease (AID) are usually excluded from ICI clinical trials. Due to a large number of cancer patients with preexisting AID, the safety and efficacy of ICIs in these patients deserve more attention. This review summarizes and analyzes the data regarding ICI therapy in cancer patients with preexisting AID from 17 published studies. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 74 publications
0
32
1
Order By: Relevance
“…In this study, OS was similar regardless of concomitant corticosteroid use, but the reason for use could not be identified from available data. The efficacy of immune checkpoint inhibitors in patients with autoimmune disease appears to be comparable to the general oncologic population, and is associated with a higher but manageable incidence of immune-related AEs [28]. In this study, patients with and without autoimmune disease had a similar rate of TRAEs and median OS, although the estimated 1-year and 2-year OS rates were numerically slightly lower in the subgroup with autoimmune disease.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, OS was similar regardless of concomitant corticosteroid use, but the reason for use could not be identified from available data. The efficacy of immune checkpoint inhibitors in patients with autoimmune disease appears to be comparable to the general oncologic population, and is associated with a higher but manageable incidence of immune-related AEs [28]. In this study, patients with and without autoimmune disease had a similar rate of TRAEs and median OS, although the estimated 1-year and 2-year OS rates were numerically slightly lower in the subgroup with autoimmune disease.…”
Section: Discussionmentioning
confidence: 50%
“…Other authors also reported responses in CSCC patients who have undergone kidney transplantation or with leukemia ( 14 , 23 , 24 ) as well as in patients treated with immunosuppressive drugs for an autoimmune disease ( 23 , 24 ). In immunosuppressed patients, the likelihood of a response to PD-1 blockade has been demonstrated also in other cancers ( 38 40 ).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, inflammatory bowel disease patients are at a higher risk of flares than rheumatoid diseases ( 77 ). Studies have shown that ICIs are equally effective in AD patients but need close monitoring for flare-ups and irAEs ( 78 , 79 ).…”
Section: Patient-specific Risk Factors For Iraementioning
confidence: 99%